1999
DOI: 10.1093/intimm/11.3.417
|View full text |Cite
|
Sign up to set email alerts
|

CD26/dipeptidyl peptidase IV differentially regulates the chemotaxis of T cells and monocytes toward RANTES: possible mechanism for the switch from innate to acquired immune response

Abstract: CD26, a 110 kDa cell surface glycoprotein, exhibits dipeptidyl peptidase IV (DPPIV; EC 3.4.14.5) enzyme activity and plays an important role in T cell co-stimulation. In the present study, the function of CD26/DPPIV in transendothelial migration was examined using beta-chemokines as chemoattractants. When soluble recombinant CD26 (sCD26/DPPIV+) was added to the transendothelial chemotaxis system, chemotactic migration of T cells toward RANTES was significantly enhanced. Addition of sCD26 to 50 ng/ml of RANTES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 37 publications
(29 reference statements)
0
68
1
Order By: Relevance
“…To study the possible influence of chemokines on the cell surface expression of TSP-1, we exposed anti-CD3-activated lymphocytes (generally Ͼ92% CD3 positive cells) in suspension and on a fibronectin substrate to CXCL12 and CCL5, two chemokines processed by CD26 (53,54). The cells were cultured in serum-free medium to exclude interference of exogenous TSP-1.…”
Section: Cxcl12 and Ccl5 Induce Cell Surface Expression Of Tsp-1 And mentioning
confidence: 99%
See 1 more Smart Citation
“…To study the possible influence of chemokines on the cell surface expression of TSP-1, we exposed anti-CD3-activated lymphocytes (generally Ͼ92% CD3 positive cells) in suspension and on a fibronectin substrate to CXCL12 and CCL5, two chemokines processed by CD26 (53,54). The cells were cultured in serum-free medium to exclude interference of exogenous TSP-1.…”
Section: Cxcl12 and Ccl5 Induce Cell Surface Expression Of Tsp-1 And mentioning
confidence: 99%
“…1 suggested that chemokines metabolized by CD26, such as CXCL12 and CCL5 (53,54,58), that cleave Nterminal dipeptides from various chemokines regulate the cell surface expression of CD91 and TSP-1 through CD26. Therefore, we examined the possible influence of the CD26 inhibitors diprotin A, KR 62436, and vildagliptin on the cell surface expression of TSP-1 in anti-CD3-activated lymphocytes using quantitative immunocytochemistry and SDS-PAGE of immunoprecipitated biotinylated cell surface proteins (Fig.…”
Section: Cd26 Influences Cell Surface Expression Of Tsp-1mentioning
confidence: 99%
“…Truncation of the cytokine RANTES (regulated on activation, normal T cell-expressed and secreted) by CD26 changes the specificity of receptor interactions and target cells, and this might be a physiologically significant control mechanism [186][187][188].…”
Section: Bp-1/6c3 (Glutamyl Aminopeptidase Ec 34117)mentioning
confidence: 99%
“…The CXCR4 natural ligand SDF-1␣ has the conserved NH 2 -X-Pro sequence (where X is any amino acid) at the NH 2 terminus, which is a consensus sequence for substrates of dipeptidyl peptidase IV activity of CD26. It has been demonstrated that SDF-1␣ can be processed by CD26 (4,9,11,32). Therefore the CD26⅐CXCR4 complex is likely a functional unit in which the expression of CD26 on the cell surface may modulate SDF-1␣-induced chemotaxis.…”
Section: Discussionmentioning
confidence: 99%